Analisis komposisi dan timbulan sampah di kawasan wisata pantai pasir putih, Kabupaten Manokwari, Provinsi Papua Barat - S. Warami, Marsya; Kaber, Yuanike; Raharjo, Syafrudin (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: Marine tourism is one of the region's leading sectors, significantly contributing to Regional Own-Source Revenue (PAD - Pendapatan Asli Daerah). However, tourist areas also generate waste from tourists or visitors. This study aims to identify and analyze the waste generation and composition in the Pasir Putih Beach tourist area and assess the potential for waste reduction. The research was conducted over four months (March-June 2024), with the study site located at Pasir Putih Beach. Waste generation measurements were categorized by source type: point sources and line sources. Point sources include restaurants and food stalls within the Pasir Putih Beach area, while line sources refer to marine debris along the shoreline. Waste generation from point sources was measured using the standard method outlined in SNI 19-2964-1994, which details the sampling and measurement of urban waste generation and composition. Based on the study's findings, 15 different types of marine debris were identified at Pasir Putih Beach. The most abundant components of marine debris were coconut shells (27.59%), wood (18.32%), and recycled plastic (14.61%). Organic waste generated by restaurants or cafés at Pasir Putih Beach amounted to 8 kg per unit per day, with a waste density of 0.007125 kg/m³ for cafés, while food stalls had a waste density of 0.00675 kg/m³. The average waste produced by food stalls at Pasir Putih Beach was 8 kg per unit per day, with a waste density of 0.00675 kg/m³. Waste from tourist activities, including cafés, restaurants, and food stalls, was primarily composed of kitchen waste and food leftovers, along with garden waste, such as leaves, accounting for 13.48% of the total. This waste can be processed through biological methods, such as composting or biodigesters.